Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1071100720919029
|View full text |Cite
|
Sign up to set email alerts
|

Return to Sport and Patient Satisfaction at 5-Year Follow-up After Nonoperative Treatment for Acute Achilles Tendon Rupture

Abstract: Background: There is controversy whether nonoperative or operative treatment for Achilles tendon rupture is superior. It is unknown if patients with acute Achilles tendon rupture return to previous sports activity. The purpose of this study was to assess 5-year return to sport and subjective satisfaction, minimum 1-year functional outcomes, and complications in patients following nonoperative treatment of Achilles tendon rupture with early weightbearing rehabilitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 38 publications
(69 reference statements)
0
22
0
Order By: Relevance
“…Despite numerous high-evidence studies, the optimal management of the ATR, conservative or operative, continues to be a subject of debate within the orthopedic community [ 7 ]; the superiority of one type of procedure over the other has not yet been demonstrated by comparing the results of the different procedures described in the literature: open, minimally invasive, or percutaneous [ 38 ]. Currently, operative treatment is particularly recommended in active patients who require a rapid return to daily activities, including sports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite numerous high-evidence studies, the optimal management of the ATR, conservative or operative, continues to be a subject of debate within the orthopedic community [ 7 ]; the superiority of one type of procedure over the other has not yet been demonstrated by comparing the results of the different procedures described in the literature: open, minimally invasive, or percutaneous [ 38 ]. Currently, operative treatment is particularly recommended in active patients who require a rapid return to daily activities, including sports.…”
Section: Discussionmentioning
confidence: 99%
“…ATR incidence has constantly increased due to aging of the population, growing prevalence of obesity, and increasing practice of sports [ 4 , 5 ]. Acute ruptures of the AT occur most frequently in middle-aged men, an incidence of 69 per 100,000, especially in those participating in sports with energetic repetitive jumping that use eccentric loading and sprinting movements that require pushing-off force [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The return to sport times ranged from 12 to 28 weeks when analyzing the different levels of return to sport. It could be stated that these return to sport times and rates are adequate in comparison to other foot and ankle sports-related injuries, such as when considering osteochondral lesions of the talus, Lisfranc injuries, and syndesmotic injuries, for example [ 8 , 14 , 21 , 24 ]. Steman et al [ 21 ] found a mean rate of 88% for RTS at any level in patients treated for osteochondral lesions of the talus treated with arthroscopic bone marrow stimulation, while a RTS at pre-injury level and type of sport of 79% was found for the same surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Several treatment options have been recommended, including immediate immobilization, open repair, percutaneous repair, and functional rehabilitation (2)(3)(4). Conventionally, the open repair was favored secondary to its lower re-rupture rates, however in more recent years, and there has been a progressive shift away from surgical intervention to reduce wound complications (5,6). On the other hand, conservative options have been shown to carry an increased rate of re-rupture and tendon lengthening and other long-term complications (7,8).…”
Section: Introductionmentioning
confidence: 99%